2020
DOI: 10.3390/jfb11020044
|View full text |Cite
|
Sign up to set email alerts
|

Time-Transient Effects of Silver and Copper in the Porous Titanium Dioxide Layer on Antibacterial Properties

Abstract: Recently, silver (Ag) and copper (Cu) have been incorporated into a titanium (Ti) surface to realize their antibacterial property. This study investigated both the durability of the antibacterial effect and the surface change of the Ag- and Cu-incorporated porous titanium dioxide (TiO2) layer. Ag- and Cu-incorporated TiO2 layers were formed by micro-arc oxidation (MAO) treatment using the electrolyte with Ag and Cu ions. Ag- and Cu-incorporated specimens were incubated in saline during a period of 0–28 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…MAO easily and selectively incorporates the required elements into the titanium surface owing to the compositional control in the electrolyte. Table 2 summarizes the published articles related to the one-step MAO-based incorporation of antibacterial elements onto the Ti surface [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. It should be noted that some researchers have combined MAO and other surface modification processes [ 103 , 104 , 105 , 106 ].…”
Section: Micro-arc Oxidation (Mao)mentioning
confidence: 99%
See 2 more Smart Citations
“…MAO easily and selectively incorporates the required elements into the titanium surface owing to the compositional control in the electrolyte. Table 2 summarizes the published articles related to the one-step MAO-based incorporation of antibacterial elements onto the Ti surface [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. It should be noted that some researchers have combined MAO and other surface modification processes [ 103 , 104 , 105 , 106 ].…”
Section: Micro-arc Oxidation (Mao)mentioning
confidence: 99%
“…Therefore, the biodegradation behavior must be precisely characterized to understand its antibacterial effect and durability. Our previous studies [ 97 , 102 ] simulated the biodegradation behaviors of Ag-, Cu-, and Zn-incorporated Ti surfaces by immersion in physiological saline for 28 days to investigate the changes in surface composition, chemical states, and antibacterial effects. The surface concentrations of Ag, Cu, and Zn were dramatically decreased by incubation for up to 7 days and remained at slight amounts until 28 days ( Figure 4 a).…”
Section: Time-transient Effects Of Ag Cu and Zn On Their Antibacmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preparation process, the phase transformation of antibacterial active metals inevitably occurs, such as during electrochemical treatments or powder processing at high temperatures, which may lead to the oxidation of the metal. Shimabukuro et al [186] embedded Cu in the TiO 2 layer on the implant surface using MAO. They found that Cu existed in the form of Cu 2 O and exerted an antibacterial effect.…”
Section: Coppermentioning
confidence: 99%
“…Ionescu et al [ 12 ] have looked to the synergistic antibacterial performance of toothpaste containing nano-hydroxyapatite substituted with metal ions. Shimabukuro et al [ 13 ] have investigated both the durability of the antibacterial effect and the surface change of Ag- and Cu-incorporated porous titanium dioxide (TiO 2 ) layer; silver (Ag) and copper (Cu) have been incorporated into the titanium (Ti) surface to realize their antibacterial properties. Ag- and Cu-incorporated TiO 2 layers were formed by micro-arc oxidation (MAO) treatment using the electrolyte with Ag and Cu ions.…”
mentioning
confidence: 99%